Gasgas silicon carbide plant - Arenas, Rosalinda R.; de Ungria, Leticia A.; Villamin, Wilfredo R.; Felix, Bienvenido E. (College of Engineering, 1974)
A proposed plant for the manufacture of SiC, having an annual capacity of 30,000 kg has been designed for future establishment. The plant is to be located at Iligan City, near the Ma. Cristina Falls. The product obtained from this plant is in the form of SiC crystals and SiC flour with a 97% purity. The land area necessary for the establishment of this plant is 6240 sq. ft. with enough space already for expansion. The building is one-story. The total capital investment is approximately P 8,195,968 of which P 7,749,577 is the fixed capital investment and the rest are operational costs. The sales/yr is P 216,900/year which makes the plant economically not feasible.